Exclusive Breastfeeding and the Incidence of Stunting in Toddlers - Mariani, Rina; Puspitarini, Zenni (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Stunting is a condition of growth failure due to chronic malnutrition, resulting in children being too short for their age, and typically occurs in toddlers. The occurrence of stunting in toddlers is influenced by several interrelated multifactorial causes. Stunting prevention can be achieved by fulfilling nutritional needs during the First 1000 Days of Life. This study aimed to determine the relationship between exclusive breastfeeding and the incidence of stunting. This was a quantitative study using a cross-sectional design, conducted at the Kemalo Abung Health Center from July to October 2024. The respondents consisted of 92 participants selected using a purposive sampling technique. The inclusion criteria were mothers with toddlers aged 2–3 years. Data collection instruments included a questionnaire and a microtoise. Data were analyzed using the chi-square test. The results showed that there was no significant relationship between exclusive breastfeeding and the incidence of stunting (p-value = 0.814).